How do you convert #x^2 + y^2 = 49# into parametric equations?
See below
There are infinite ways of do that
Ex.
By signing up, you agree to our Terms of Service and Privacy Policy
To convert the equation (x^2 + y^2 = 49) into parametric equations, we can use the trigonometric parameterization. Let (x = 7\cos(t)) and (y = 7\sin(t)), where (t) is a parameter ranging from (0) to (2\pi).
Substituting these expressions into the equation (x^2 + y^2 = 49), we get:
[(7\cos(t))^2 + (7\sin(t))^2 = 49] [49\cos^2(t) + 49\sin^2(t) = 49] [49(\cos^2(t) + \sin^2(t)) = 49] [49 = 49]
This is true for all values of (t) from (0) to (2\pi). Hence, the parametric equations for the circle (x^2 + y^2 = 49) are:
[x = 7\cos(t)] [y = 7\sin(t)]
Where (t) ranges from (0) to (2\pi).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you find the length of the curve #x=t/(1+t)#, #y=ln(1+t)#, where #0<=t<=2# ?
- For #f(t)= (sint,cos^2t/t)# what is the distance between #f(pi/4)# and #f(pi)#?
- Given Parametric equations: #x = 2(t)^2# and y = 4t how do you find the cartesian equation?
- What is the arc length of teh curve given by #r(t)=(2t , 2e^(-t) , e^(t) )# in the interval #t in [0,3]#?
- What is the arc length of #f(t)=((4-t^2)e^t,te^t) # over #t in [3,4] #?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7